Weighted tree-walking automata - Fülöp, Zoltán; Muzamel, Loránd (Acta Cybernetica, 2009)
We define weighted tree-walking automata. We show that the class of tree series recognizable by weighted tree-walking automata over a commutative semiring K is a subclass of the class of regular tree series over K. If K is not a ring, then the inclusion is strict.